PENGARUH PENGENDALIAN INTERN DAN SUMBER DAYA MANUSIA BIDANG AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH (Studi Pada SKPD di Kabupaten Tebo) - Anis Maghfiroh; Muhammad Rasuli; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of internal control and human resources to the quality of local government financial reports. This research is quantitative. The population in this study section finance / accounting at SKPD in Tebo regency, where the number 26 SKPD studied. 104 questionnaires were distributed and the number of questionnaires that can be analyzed as much as 76 questionnaires. Data collection method is by distributing questionnaires. Data analysis techniques using multiple regression t test using SPSS software version 20.0.Results from this study showed that the variables of internal control and human resources in accounting affects the quality of local government financial reports. For government agencies are expected to improve the quality of performance in terms of financial management with attention and improve the quality of its human resources adequate accounting internal control in order to produce financial statements quality of local government.Keywords: internal control , human resources, financial reports, and government